Implementasi Fatwa DSN-MUI Dalam Jual Beli Emas Secara Tidak Tunai Di Bank Syariah Indonesia - Meilianingsih, Fanisa; Fateh, Mohammad; M. Zain, Noorma Fitriana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to analyze the mechanism of buying and selling gold in cash in gold installment products at Bank Syariah Indonesia (BSI) and analyze the application of fatwa number 77/DSN-MUI/V/2010 concerning the cashless buying and selling of gold in gold installment products at BSI. The type of research used is juridical-empirical research and uses a qualitative approach. The source of research data was obtained from the results of interviews through parties concerned with BSI gold installment products, secondary data sources were obtained from the internet, books, relevant previous research and other written sources related to the research. The results of the study show that the implementation of fatwa number 77/DSN-MUI/V/2010 concerning the sale and purchase of gold in cash on BSI gold installment products is not in accordance with what is in the limits and provisions in the fatwa. The selling price of gold (tsaman) is not allowed to increase during the term of the agreement even though there has been an extension of the period after maturity. Gold purchased with credit or cashless payment can be used as collateral (rahn). And gold that is used as collateral may not be sold or used as an object of other contracts that cause a transfer of ownership. The contribution of this research is that it can be an evaluative reference for strengthening the implementation of sharia principles in non-cash gold financing products.